Effect of Granotsit preparation on mesenchymal bone marrow stem cells in experimental model of secondary immune deficiency with the aid of cyclophosphan - A. N. Baikov; V. P. Shakhov; N. Yu. Shelgaev; V. A. Serebryakova (Бюллетень сибирской медицины)
Experiments with 60 male and female mice of Balb/c line with mass of 18—21 g have been carried out. All manipulations, including ether euthanasia, were performed within the framework of approved rules for experiments with experimental animals. The mice were divided into four groups each of 15 animals. The groups were injected with physiological salt solution (first group), cycliphosphan (second group), Granotsit preparation (recombinant granulocytic colony-stimulating factor) (third group), and cycliphosphan in Granotsit preparation (fourth group). We have studied the total number of leucocytes in blood, bone marrow cellularity, content of granulocytic- macrophage colony-forming cells and mesenchyma l precursors with the aid of tissue culture in vitro. It has been found that the Granotsit preparation can stimulate myelopoiesis (direct specific action) and mesenchymopo iesis (indirect action) in norm. When a cytostatic agent, the studied cytokine has a protective action on both myeloid and mesenchyma l precursors of bone marrow.